Sliding Mode Control for a Class of Linear Infinite-Dimensional Systems - Balogoun, Ismaila; Marx, Swann; Plestan, Franck (IEEE transactions on automatic control, 2025)
This article deals with the stabilization of a class of linear infinite-dimensional systems with unbounded control operators and subject to a boundary disturbance. We assume that there exists a linear feedback law that makes the origin of the closed-loop system globally asymptotically stable in the absence of disturbance. To achieve our objective, we follow a sliding mode strategy, and we add another term to this controller in order to reject the disturbance. We prove the existence of solutions to the closed-loop system and its global asymptotic stability, while making sure the disturbance is rejected.